Molecular Characterization and Pathogenicity Analysis of Alternaria alternata Associated with Leaf Spot Disease of Toona sinensis in China - Xiansheng Geng; Huyun Mvchir; Jun Liu; Keda Hua; Qiang Miao; Jinping Shu (Horticulturae)
The tree species Toona sinensis has been cultivated in China for over 2000 years for multiple purposes. In 2022, leaf spots were detected on the leaves of T. sinensis in a germplasm resource nursery in Zhejiang Province, China. Symptomatic leaves were collected, and fungal isolation was conducted. Four fungal isolates resembling Alternaria were isolated from the diseased leaves. These isolates were identified as Alternaria alternata according to a combination of morphological characteristics and multigene phylogenetic analysis. To fulfill Koch’s postulates, the pathogenicity of the selected isolate, YKHH, was tested on 2-year-old container seedlings of T. sinensis. Disease symptoms basically consistent with those observed in the field developed 12 days after inoculation (DAI) when either conidia or mycelia were used as the inoculum. Nevertheless, no visible symptoms developed on the leaves of the control groups. The fungi were reisolated from the diseased leaves, and both the morphological characteristics and three gene sequences (GAPDH, RPB2, and TEF1-α) of the reisolated fungi were consistent with those of the original YKHH isolate. Susceptibility trial results showed that family 55 of T. sinensis (F55) had the highest susceptibility to A. alternata, while family 28 of T. sinensis (F28), family 52 of T. sinensis (F52), and Toona ciliata var. pubescens (TCP) exhibited equal susceptibility to A. alternata. To the best of our knowledge, this is the first report of leaf spot disease caused by A. alternata on T. sinensis in China.